AN EMPIRICAL STUDY ON THE CONSEQUENCES OF ORGANIZATIONAL CYNICISM - Kürü, Seval Aksoy; Demirel, Oğuz (Beykent Üniversitesi, 2021)
The aim of this research is to investigate the effects of cognitive, affective and behavioral cynicism sub-dimensions of organizational cynicism on organizational policy perception, work engagement, organizational dissent, and organizational identification. The data of the research was collected from 735 employees working in organizations operating in the pharmaceutical industry in İstanbul in 2019 by survey method. The obtained data were analyzed with SPSS and structural equation modeling (SEM-AMOS) package programs. According to the structural equation modeling findings, while cognitive cynicism, one of the sub-dimensions of organizational cynicism, has a significant effect on organizational policy perception, organizational dissent, and organizational identification; no significant effect was found on work engagement. Affective cynicism has a significant effect on work engagement, organizational dissent, perception of organizational policy, and organizational identification. Finally, behavioral cynicism does not seem to have a significant effect on work engagement, and organizational identification; it has been seen that it has a significant effect on organizational policy perception and organizational dissent. Depending on all these results, it is understood that organizational cynicism has a negative effect on work engagement and organizational identification, and a positive effect on organizational policy perception and organizational dissent.

Bu araştırmanın amacı, örgütsel sinizmin ardılları üzerindeki etkilerini tespit etmektir. Araştırma verisi pazarlama ve satış sektöründe hizmet veren 735 satış personelinden anket yöntemi ile toplanmıştır. Elde edilen veriler yapısal eşitlik modeli ile analiz edilmiştir. Yapısal eşitlik modellemesi bulgularına göre örgütsel sinizmin alt boyutlarından bilişsel sinizmin işe adanmışlık üzerinde anlamlı bir etkisi bulunamamıştır. Benzer şekilde, davranışsal sinizm alt boyutunun da işe adanmışlık üzerinde istatistiksel açıdan anlamlı bir etkisi tespit edilememiştir. Diğer yandan duygusal sinizm boyutunun işe adanmışlık üzerinde negatif ve anlamlı bir etkisi bulunmaktadır. Örgütsel sinizmin örgütsel muhalefet üzerindeki etkilerine bakıldığında; bilişsel sinizmin örgütsel muhalefet üzerinde negatif ve anlamlı, duygusal sinizmin pozitif ve anlamlı ve davranışsal sinizmin pozitif ve anlamlı etkileri mevcuttur. Bilişsel sinizmin örgütsel politika algısı üzerinde pozitif ve anlamlı, duygusal sinizmin pozitif ve anlamlı ve davranışsal sinizmin pozitif ve anlamlı etkileri olduğunu göstermektedir. Son olarak örgütsel sinizmin alt boyutlarından, bilişsel sinizmin örgütsel özdeşleşme üzerinde negatif ve anlamlı ve duygusal sinizmin negatif ve anlamlı etkileri tespit edilmiştir. Ancak, davranışsal sinizmin örgütsel özdeşleşme üzerinde anlamlı bir etkisi mevcut değildir.
ÖRGÜTSEL SİNİZMİN ARDILLARI ÜZERİNE GÖRGÜL BİR ARAŞTIRMA